PENGARUH WORK OVERLOAD DAN EMOTIONAL DISSONANCE TERHADAP BURNOUT DENGAN RESILIENSI SEBAGAI VARIABEL MODERATING PADA KARYAWAN PT.PLN UP3 PADANG - Fadil Muhammad; Laura Syahrul; Yulihasri (Journal Publicuho, 2025)
Burnout in the work environment is becoming more frequent as the demands and emotional pressures felt by employees increase. This study aims to analyse the influence of work overload and Emotional dissonance on burnout, as well as explore the role of resilience as a moderation variable in these relationships. The study uses a quantitative approach by testing five main hypotheses. The results of the analysis showed that work overload had a significant effect on burnout (t = 3.009; p = 0.003; o = 0.319), as well as Emotional dissonance, which also had a significant positive effect (t = 3.235; p = 0.001; o = 0.375). Although resilience did not directly have a significant effect on burnout (t = 1.619; p = 0.105; o = -0.159), this variable was shown to moderate the relationship between work overload and burnout (t = 1.998; p = 0.046; o = 0.231), as well as between Emotional dissonance and burnout (t = 2.151; p = 0.032; o = -0.196). Organisations are advised to develop resilience-building programs to maintain employees' mental health and create a more adaptive and productive work environment.